THE Javanese Feminine Leadership during the Pandemic: A study of Sragen Regent’ s leadership style in overcoming the Covid-19 Pandemic - Setyasih Harini; Riska Wirawan (Salasika, 2022)
This research aims to describe the female regional head presented by Sragen Regent to overcome with Covid-19 colored with feminine leadership style and Javanese-Surakarta culture. In certain situations, feminine leadership styles characterized by being attentive, humble, empathetic, and close to people are more appropriate and have a positive impact. Sragen Regent dr. Hj. Kusdinar Untung Yuni Sukowati is the first woman to be a Regional Leader raised Surakarta patriarchic cultural environment but her presence as a female regent with local culture. As the nature of the research, this study conducts a qualitative descriptive approach with feminine theory on political leadership styles and philosophy of Javanese-Surakarta leadership style. The result of the research shows the success of the political leadership style presented by Sragen Regent in overcoming Covid-19 by combining and synergizing feminine leadership style and implementing the 5-M: Melek (attentive and introspective), Milik (having a sense of belonging), Muluk (fulfill the daily needs), Melok (empathetic), and Meluk (being close to the people) based on leadership value of Serat Wedhatama. As a leader and a member of Sragen society all at once, the regent shows cooperation and involves the people in socializing and supervising the implementation of health protocol to pursue social welfare.